Proposed healing yoga centre at Leisure Farm Resort residences, Johor Bahru - 491188 Tan, Yin Chirn; Zainul Hakim Mohd. Zain, supervisor; Fakulti Alam Bina (2009)
Project Paper (Sarjana Muda (Senibina Landskap)) - Universiti Teknologi Malaysia, 2009